A Geospatial Analysis of Early Psychosis Intervention Programs in Toronto, Canada: Une analyse géospatiale des programmes d’intervention précoce en cas de psychose à Toronto, au Canada - Rotenberg, Martin; Graffi, Justin; Anderson, Kelly; Kurdyak, Paul; Kozloff, Nicole; Foussias, George (Canadian journal of psychiatry, 2025)
ObjectivesEarly psychosis intervention (EPI) programs play a crucial role in detecting and treating psychosis early, yet disparities in access persist. This study aimed to assess the spatial accessibility of EPI programs in Toronto, Canada, and to explore the association between access and indicators of neighbourhood-level marginalization.MethodsWe conducted a geospatial analysis using floating catchment area and two-step floating catchment area methods, examining EPI program locations, census population estimates for the 158 Toronto neighbourhoods, and area-level marginalization data. Spatial regression models were used to estimate the association between marginalization factors and spatial accessibility.ResultsOn average, the closest EPI program is 4 km away from the centre of any given neighbourhood (range 0.8-11 km), with variability across the city. Clustering is observed in some neighbourhoods, indicating better spatial accessibility, whereas other neighbourhoods face lower access. A full spatial regression model showed increasing levels of housing and dwelling marginalization, as well as material resource marginalization, to be associated with better access.ConclusionWe identified neighbourhoods that have poorer spatial accessibility to EPI services. Some neighbourhood-level marginalization indicators previously found to be associated with psychosis risk are also associated with better spatial accessibility. It is notable that EPI services in Toronto may be located where they are most needed the most. The study underscores the importance of geospatial analyses to identify and address geographic distance as a potential source of disparity in access.